SODIUM IN BREAD PRODUCED BY SUPERMARKETS IN GOIÂNIA (GO), BRAZIL - Carvalho, Ana Clara Martins e Silva; Teixeira, Luana Borges; Gondim, Ítalo Careli (Journal of Health Care, 2015)
Objective: Analyze the sodium content in bread rolls from the bakeries of a large-scale supermarkets chainin Goiânia (GO), Brazil. Materials and Methods: This is a descriptive observational study carried out atthree in-store bakeries of a 12-store supermarket chain. The sodium level was quantified by monitoring allstages of the bread roll production process and through direct weighing of ingredients. The Brazilian FoodComposition Table was used for calculations. The salt and sodium levels obtained were compared withWorld Health Organization (WHO) recommendations, with the National Sanitary Surveillance Agency’s(ANVISA) goals for the reduction of sodium levels in bread rolls produced in Brazil, with UK Food StandardsAgency’s classification of food sodium levels and with a proposed sodium level classification based onBrazilian legislation. Variance analysis was used to compare data between different bakeries. Results: Thesodium levels found in bread rolls are above those proposed by the National Sanitary Surveillance Agencyand those found in the main tables used for quantifying food nutrients in the field of nutrition. The rollswere classified as having high sodium levels (>600 mg/100 g). Conclusion: These supermarkets needto review their standardized recipe to reduce bread sodium levels and offer a more healthful and higherquality product to the population.